2022
DOI: 10.1111/papt.12383
|View full text |Cite
|
Sign up to set email alerts
|

How social rejection expectations and depressive symptoms bi‐directionally predict each other – A cross‐lagged panel analysis

Abstract: Background: Although research suggests that social rejection expectations play a crucial role in the development and maintenance of depressive symptoms, it is not clear whether such expectations are a risk factor for depression or rather a consequence thereof. The present study addressed this issue by investigating the time-lagged bi-directional effects of social rejection expectations and depressive symptoms. Methods: In an online survey, participants (N = 347) completed measures of social rejection expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…For example, our findings from the "Interpersonal Rejection" subscale indicate good convergent validity in conjunction with rejection sensitivity, depressive expectations, interpersonal problems, interpersonal trust, and perceived social support, as the relationships appeared in expected directions and of expected magnitudes. These findings are also consistent with previous findings that DIBs of social rejection are associated with the aforementioned constructs (for emperical studies, e.g., Croft & Zimmer-Gembeck, 2014;Kirchner et al, 2022;Kube et al, 2017;Zielinski & Veilleux, 2014; for research-syntheses, e.g., Gao et al, 2017;Poggi et al, 2019;Romero-Canyas et al, 2010).…”
Section: German Version Of the Interpersonal Cognitive Distortions Scalesupporting
confidence: 92%
See 2 more Smart Citations
“…For example, our findings from the "Interpersonal Rejection" subscale indicate good convergent validity in conjunction with rejection sensitivity, depressive expectations, interpersonal problems, interpersonal trust, and perceived social support, as the relationships appeared in expected directions and of expected magnitudes. These findings are also consistent with previous findings that DIBs of social rejection are associated with the aforementioned constructs (for emperical studies, e.g., Croft & Zimmer-Gembeck, 2014;Kirchner et al, 2022;Kube et al, 2017;Zielinski & Veilleux, 2014; for research-syntheses, e.g., Gao et al, 2017;Poggi et al, 2019;Romero-Canyas et al, 2010).…”
Section: German Version Of the Interpersonal Cognitive Distortions Scalesupporting
confidence: 92%
“…Second, our study's cross-sectional design enabled us to draw conclusions neither about the temporal stability of the ICDS and its subscales nor about the temporal precedence of DIBs and clinical outcomes. Future investigations of whether DIBs temporally precede or succeed important psychopathological indices seem eminently worthwhile to us, as they would shed light on whether DIBs should be considered a risk factor for or rather a consequence of mental disorders (Kirchner et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we detected a strong relationship between ostracism and paranoid thoughts, which supports the suggestion of bi-directionality between the two constructs. As such, we suggest future researchers consider examining the link between perceived ostracism and the onset of paranoid thoughts more closely by adopting longitudinal designs (e.g., utilizing cross-lagged designs; see Kirchner et al, 2022). Secondly, all data collected was self-report which increases the risk of common method bias.…”
Section: Discussionmentioning
confidence: 99%
“…All levels and variations on measures used to assess psychopathology were comparable with other samples drawn from the general population. Previous observations include M = 5.99 ( SD = 4.67) with n = 72 for social anxiety [ 74 ], M = 9.46 ( SD = 4.76) with n = 347 for rejection sensitivity [ 75 ], M = 17.49 ( SD = 4.39) with n = 1141 for trait anxiety [ 76 ], M = 3.30 ( SD = 3.65) with n = 2693 for depression levels [ 76 ], M = 0.94 ( SD = 1.14) with n = 4360 for eating psychopathology [ 66 ], M = 6.09 ( SD = 4.13) with n = 634955 for systemizing [ 39 ], M = 9.83 ( SD = 4.98) with n = 634955 for empathizing [ 39 ], M = 50.07 ( SD = 11.06) with n = 965 for alexithymia [ 68 ] and M = 30.04 ( SD = 6.13) with n = 752 for impulsivity [ 71 ]. When studies reported questionnaire data separated by gender, we pooled data across gender categories with pooled variance defined as the mean of the variances plus the variance of the means of each data set [ 77 ].…”
Section: Methodsmentioning
confidence: 99%